PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KUALITAS PENGUNGKAPAN INFORMASI TANGGUNG JAWAB SOSIAL DAN DAMPAKNYA PADA NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Publik Di Bursa Efek Indonesia) - Ade Adriani (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This research was intended to examine : (1) the effect of Corporate Social Responsibility activities (consisting of social responsibility, product responsibility, labor practices responsibility and environmental responsibility) related to the quality of social responsibility information disclosures, and (2) the effect of Corporate Social Responsibility activities (consisting of social responsibility, product responsibility, labor practices responsibility, environmental responsibility) and the quality of social responsibility information disclosures to firm value. The samples of this research are taken from 69 public companies whiches distributed dividend payments during 2007-2008, and publicly released information of their Corporate Social Responsibility activities in their annual reports, Sustainability Reports and/or other Corporate Social Responsibility reports in the year of 2008. This research applies primary and secondary data sources. Based on the results of the data analysis and discussion, these are the following research findings : (1) there is a positive and significant influence of corporate social responsibility activities (consisted of social responsibility, product responsibility, labor practices responsibility, and environmental responsibility) on the quality of corporate social responsibility information disclosure, (2) there is a positive and significant influence of social responsibility, product responsibility, labor practices responsibility, environmental responsibility and the quality of corporate social responsibility information disclosure on firm value. This research indicates corporate social responsibility activities (consisting of social responsibility, product responsibility, labor practices responsibility, environmental responsibility) and the quality of corporate social responsibility information disclosure has a positive and significant effect on firm value. At the same time, this research also shows that corporate social responsibility activities have a positive indirect effect to firm value with the quality of corporate social responsibility information disclosure as an intervening variable.